The interleukin-6-activated acute-phase response factor is antigenically and functionally related to members of the signal transducer and activator of transcription (STAT) family. - Wegenka, U M (1994)
Interleukin-6 (IL-6), leukemia inhibitory factor, oncostatin M, IL-11, and ciliary neurotropic factor are a family of cytokines and neuronal differentiation factors which bind to composite plasma membrane receptors sharing the signal transducing subunit gp130. We have shown recently that IL-6 and leukemia inhibitory factor rapidly activate a latent cytoplasmic transcription factor, acute-phase response factor (APRF), by tyrosine phosphorylation, which then binds to IL-6 response elements of various IL-6 target genes. Here we demonstrate that APRF is activated by all cytokines acting through gp130 and is detected in a wide variety of cell types, indicating a central role of this transcription factor in gp130-mediated signaling. APRF activation is also observed in vitro upon addition of IL-6 to cell homogenates. Protein tyrosine kinase inhibitors block both the tyrosine phosphorylation and DNA binding of APRF. The factor was purified to homogeneity from rat liver and shown to consist of a single 87-kDa polypeptide, while two forms (89 and 87 kDa) are isolated from human hepatoma cells. As reported earlier, the binding sequence specificity of APRF is shared by gamma interferon (IFN-gamma) activation factor, which is formed by the Stat91 protein. Partial amino acid sequence obtained from purified rat APRF demonstrated that it is likely to be related to Stat91. In fact, an antiserum raised against the amino-terminal portion of Stat91 cross-reacted with APRF, suggesting the relatedness of APRF and Stat91. Altogether, these data indicate that APRF belongs to a growing family of Stat-related proteins and that IFN-gamma and IL-6 use similar signaling pathways to activate IFN-gamma activation factor and APRF, respectively.